Theoretical Issues in the Relationship between Psychology and Religion: Some Comments on Reber, Nelson, Slife and Whoolery, and Richardson - Tan, Siang-Yang 1954- (2006)
The article briefly responds to and comments on the four major articles by Reber, Nelson, Slife and Whoolery, and Richardson in this special issue of the Journal of Psychology and Theology. While a substantial case has been made for how secularized and reductionistic psychology is, and how psychology is still greatly influenced by logical positivism and scientism, there is a danger of overstating this case and thus throwing out the baby with thebathwater. A healthy respect for good science in psychology is still valid and possible without succumbing to scientism and logical positivism. Ultimately we need to depend on the Holy Spirit, and the community of the church and its historic traditions, to more fully appropriate truth, including biblical psychospiritual truth.